Here's the question you clicked on:
Rachel98
I need help getting started on this one. Don't give me the answer, though. So I am trying to find the solution to this linear system through substitution. { - 2x - y = 3 and y - 12 = x.
isolate y in the second equation , then substitute this into the first equation
actually it would be simpler to just substitute x from the second equation into the first ( as it is already isolated)
Oh, so to substitute we get - 2(y - 12) = 3?
yeah that's the quickest way ,
So, to solve I would distribute the 2. So I get - 2y + 24 = 3, then I subtract 24 from both sides and get - 2y = - 21, I divide both sides by - 2 and get y = 10.5? Is that right?
your working looks right , but there must be a mistake somewhere
ahh you forgot one term - 2x - y = 3 , y - 12 = x. -2(y-12)-y=3 - 2y + 24 -y =3
Since the variables are on the same side do you add them together and get - 3y?
Okay so we get - 3y + 24 = 3 and then we subtract 24 from both sides and get - 3y = - 21, then we divide both sides by negative 3 and get y = 7
very good. now just use this to find x and your done
So, we get - 2x - 7 = 3. So then we add 7 to both sides and get - 2x = 10, then we divide both sides by - 2 and get x = - 5?
\[\LARGE\color{red}{\checkmark\checkmark}\]
Thanks for the help. So the solution is (- 5, 7)?
i might have been quicker to substitute y=7 into the second equation but the result is the same (-5,7) Yes!